Pengaruh Corporate Social Responsibility (CSR), Kinerja Lingkungan, dan Green Accounting terhadap Kinerja Keuangan - Fitri Lestari; Henny Ikka Aprilia; Azizil Dwi Putra; Titik Aryati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research was purposely to analyzing the impact of green accounting, environmental performance, also corporate social responsibility (CSR) towards manufacturing operating profits listed on the Indonesia Stock Exchange from 2022 to 2024. Companies are encouraged to prioritize social and environmental elements in addition to profit-seeking due to increased expectations of sustainable business practices. This quantitative analysis relies on secondary data taken from annual reports, sustainability reports, and evaluation of the company's Environmental Management Performance Assessment (PROPER) assessment Program. Purposive sampling approach is used to take samples. Regression analysis of panel data was including use panel corrected standard errors (PCSE) method and random effect Model (REM). These findings suggest that a company's financial success is not affected by its Corporate Social Responsibility efforts or its environmental performance. Green accounting, on the other hand, the yields was shown that improve financial output significantly. According to this study, environmental information that is publicly disclosed and integrated into a company's accounting system can generate more real economic value than environmental and social initiatives that don't have significant recognized by the market as a component of profitability. The yields this research shown the important implications for business leaders who wanna incorporate environmental accounting into their sustainability strategies.